Afiliasi Mazhab Fiqh Tarekat ShÃ¢dhilÃ®yah di Jombang - Zuhdi, Zaenu (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This article attempts to look at the fiqh school affiliation of Shâdhilîyah Tariqa in Jombang which has certain patterns of worship. A set of rituals conducted by the adherents of this Tariqa show that they conducted the rituals in accordance with Shâfi?î school. However, in some cases there are few things which are quite different from the Shâfi?î school. There are two possible causes. First, the adherents of the Tariqa follow the opinion of their murshid. Second, they follow the opinion of other three Sunni schools, i.e. Hanafi, Mâlikî, and Hanbalî, though it is insignificant. Different ways of performing ritual occur when the murshid issues fatwa on different opinion from the Shâfi?î school. It means that as long as the murshid does not issue the fatwa which is different from the Shâfi?î school, the majority of the adherents remain affiliate to it. Furthermore, when the adherents study fiqh more deeply and compare the fiqh schools, they follow the stongest argument of the schools eventough it is not Shâfi?î school. However, this phenomenon is rarely happen for the adherents of the Shâdhilîyah Tariqa in Jombang as their knowledge in fiqh is not deep enough. Their affiliated school of fiqh is mosty influenced by the social and cultural conditions surrounding them as well as their education and religious knowledge.Keywords: Shâdhilîyah Tariqa, Shâfi?î school, affiliation, murshid.